Leptin/adiponectin ratio as a prognostic factor for increased weight gain in girls with central precocious puberty - Zurita-Cruz, Jessie Nallely; Villasís-Keever, Miguel Angel; Manuel-Apolinar, Leticia; Damasio-Santana, Leticia; Garrido-Magaña, Eulalia; Rivera-Hernández, Aleida de Jesús (Frontiers in Endocrinology, 2023)
Objective. To determine if the leptin, adiponectin, and leptin/adiponectin ratio (LAR) can predict weight gain at the end of GnRH analogs (GnRHa) treatment in girls with central precocious puberty (CPP). Material and methods. Study design: prospective cohort. Serum levels of leptin and adiponectin were determined at diagnosis of CPP. Anthropometry was performed at diagnosis of CPP and every six-months, until treatment with GnRHa was discontinued and they presented menarche. Patients were divided according to BMI<94 and BMI>95 percentile at diagnosis of CPP. The outcome was the increased in weight gain (e.g., from normal weight to overweight) at the end of follow-up. Statistical analysis: repeated measures ANOVA test and Student's t-test were used to compare groups. Logistic regression analysis was used to evaluate the association of leptin and adiponectin levels, as well as LAR values with increased weight gain. Results. Fifty-six CPP patients were studied, 18 had BMI >95 percentile and 38 BMI <94 percentile. Of the 18 patients who initially had BMI >95th, two patients went from obesity to overweight, while among the 38 patients who started with BMI <94th, 21 (55.2%) increased their weight gain at the end of follow-up. This last group had higher leptin levels (8.99 ± 0.6 vs 6.14 ± 0.8, p=0.005) and higher LAR values compared to those who remained in the same weight (1.3 ± 0.5 vs 0.96 ± 0.56, p=0.01). In the logistic regression analysis, it was found that higher leptin levels and higher LAR values were associated with increased weight gain (RR 1.31, 95%CI 1.03-1.66, RR 4.86, 95%CI 1.10-21.51, respectively), regardless of birth weight, pubertal stage, age, and bone/chronological age ratio. Conclusions. In patients with CPP, leptin levels and higher LAR values appear to be associated with significantly greater weight gain during GhRHa treatment, particularly in girls starting with BMI < 94 percentile.